2023
DOI: 10.7759/cureus.38908
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-Induced Acute Hepatitis

Abstract: Metformin is considered an initial oral pharmacotherapy of choice for treating hyperglycemia in type 2 diabetes mellitus (T2DM). Although safe in the vast majority of the population, rare side effects will come to light as the prevalence of T2DM continues to rise. We present a rare case of metformin-induced hepatotoxicity and possibly the first reported case of dose-dependent metformin-induced hepatotoxicity. This case report aims to make clinicians aware of this infrequent yet significant adverse reaction tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The speci c reason for a metformin-induced increase in the frailty index remain unclear. Previous studies have suggested several possible factors: 1) lactic acidosis [34] , 2) induced hepatotoxicity such as acute hepatitis [35] , 3) hypoglycemia [36] , 4) gastrointestinal adverse reactions including nausea, vomiting, and diarrhea [37] , and 5) potential myasthenia. However, the link between metformin and muscular dystrophy remains uncon rmed.…”
Section: Discussionmentioning
confidence: 99%
“…The speci c reason for a metformin-induced increase in the frailty index remain unclear. Previous studies have suggested several possible factors: 1) lactic acidosis [34] , 2) induced hepatotoxicity such as acute hepatitis [35] , 3) hypoglycemia [36] , 4) gastrointestinal adverse reactions including nausea, vomiting, and diarrhea [37] , and 5) potential myasthenia. However, the link between metformin and muscular dystrophy remains uncon rmed.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on new drugs causing iDILI, a selection of reports is listed using exclusively the updated RUCAM (Table 11) [60,94,95,. • Atezolizumab score 7, probable Tzadok, 2022 [111] • Durvalumab score 6 or 7, probable Swanson, 2022 [112] • Ceftriaxone score 6, probable Asif, 2023 [113] • Enoxaparin score 8, probable Eze, 2023 [114] • Favipiravir score 6, probable Yamazaki, 2021 [115] • Fluoroquinolones scores 6-8, probable; score ≥9, highly probable Yang, 2019 [116] • Girosivan score 8, probable Ma, 2023 [117] • Ibuprofen score 8, probable Deng, 2022 [118] • Iguratimod Score 9, highly probable Li, 2018 [119] • Ipragliflozin score 7, probable Niijima, 2017 [120] • Liraglutide score 8, probable Inayat, 2023 [121] • Metformin score 10, highly probable Mian, 2023 [122] • Methotrexate scores 6-8, probable; ≥9, highly probable Qin, 2022 [123] • Nevirapine scores 6-8, probable Giacomelli, 2018 [124] Table 11. Cont.…”
Section: Updated Rucam In Idili Cases With New Drugsmentioning
confidence: 99%